2019
DOI: 10.1177/0731684419896852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olive oil on physical and mechanical properties of ceramic waste-based geopolymer foam

Abstract: The present study concentrated on porous geopolymer composites (between calcined clay and metakaolin) using hydrogen peroxide as a pore generation agent. To reduce as well as recycle the waste from a factory, calcined clay waste was used as starting material. The geopolymer was synthesized via a geopolymerization method by a reaction with an alkaline solution, using the ceramic waste and metakaolin as raw materials. Different amount of olive oil (0–15 wt%) were added to the samples. The olive oil affected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…It could be observed that the obtained values for the compressive strength and porosity from the confirmation tests, especially for Exp-3, combined high values of compressive strength, as well as porosity. These values are superior as compared with that obtained in Table 3 of the current study, also, they are superior to that reported for the metakaolin-based geopolymer in the literatures [2,21,23,40,41] as summarized in Table 10.…”
Section: Confirmation Experimentscontrasting
confidence: 75%
See 1 more Smart Citation
“…It could be observed that the obtained values for the compressive strength and porosity from the confirmation tests, especially for Exp-3, combined high values of compressive strength, as well as porosity. These values are superior as compared with that obtained in Table 3 of the current study, also, they are superior to that reported for the metakaolin-based geopolymer in the literatures [2,21,23,40,41] as summarized in Table 10.…”
Section: Confirmation Experimentscontrasting
confidence: 75%
“…The vegetable oils is one of the interesting stablizers because of their low cost and availability. The reaction between highly alkaline solution of geopolymer and vegetable oils, by a saponification reaction, result in the interconnect porous structure [23,24].…”
Section: H2o2 → H2o + ½ O2mentioning
confidence: 99%
“…Figure 7 presents selected geopolymer components manufactured on prof sional industrial lines and tested in real conditions. There is no doubt that geopolymer technology will continue to develop intensiv [70][71][72][73][74][75][76][77][78]. A key driver for the production of geopolymer concretes is the prospect of a s nificant reduction in CO2 emissions associated with their production process compared the production of Portland cement.…”
Section: Forecast and Summarymentioning
confidence: 99%
“…In recent years, large-scale demonstration projec such as those carried out in Australia, have stimulated further basic research, especia studies on the durability of geopolymer concretes and engineering of production [13]. There is no doubt that geopolymer technology will continue to develop intensively [70][71][72][73][74][75][76][77][78].…”
Section: Forecast and Summarymentioning
confidence: 99%
“…Most of these CO polymers accelerate the synthesis of polyurethane (PU), poly­(2-hydroxyethyl methacrylate), poly­(lactic acid) (PLA), and sometimes blended with commercially available poly­(methyl methacrylate) (PMMA), polystyrene, and poly­(vinyl alcohol). Notably, unlike many other vegetable oils such as olive oil, sunflower oil, and soybean oil, etc. CO is also being used to synthesize polymers and polymeric composites for industrial and biomedical applications without disrupting the eco-system.…”
Section: Introductionmentioning
confidence: 99%